Standard Time Measurement of Sugar Brown MSMEs in Payakumbu - Marlina, Winny Alna; Armijal, Armijal; Anwar, Syaiful (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Sugar Brown MSMEs was established in 2000 in West Sumatera, Indonesia. This MSMEs produces brown sugar. This MSMEs doesn’t have time standard in the production of brown sugar, the corporation is unable to precisely estimate the number of workers required based on the workload at each work station. Many hours are lost because employees have a lengthy amount of free time to work. In order for the business to identify effective working hours and boost productivity, as well as determine daily production, the research aims to investigate standard time by accounting for the average observation time and the typical amount of time needed for employees to finish the brown sugar production process. Time study is used in the qualitative research methodology. Primary data is the source of the data. A stopwatch is used to record working time data, and Westinghouse is the type of adjustment employed. After gathering data on employee working hours, the data is tested for consistency. Operator work is examined, operator working time is computed, the number of requests to be received is estimated, the workload of each work station is determined, and the number of workers is determined based on the workload. Result of the research found that the sap water collection activity yielded research data indicating that the time taken was 108.42 minutes on average, 89.98 minutes on normal, and 113.89 minutes on standard. The sap water boiling operation took an average of 7.92 hours, 6.57 hours on average, and 8.31 hours on standard. The standard time for the Brown sugar printing operation was 92.24 minutes, the normal time was 72.87 minutes, and the average time was 87.8 minutes. The packing operation took an average of 23 minutes, 19.09 minutes on average, and 24.16 minutes on average.